Relationship between Whatsapp usage and employee engagement in ministry of communication and multimedia Malaysia - Hashim, Norliana; Mohd Shahid, Noorfazlina; Razak, Muhammad Nur Fitri (Human Resource Management Academic Research Society, 2022)
A successful organization needs to have productive employees. In order for the organization to get engaged with their employees, the new medium of communication has been used to share information, exchange opinions and as the best way to get closer with their employees. There is a dramatic change in the way of communication between employer and employee due to the change of the new technology. This situation has allowed the employee to use this new medium of communication to communicate information to their employee. It also has given the opportunity for the employee to share their opinion involving their works and the organization’s goals to their employer. Thus, this new application might give an impact on employee engagement in an organization. Due to that, in-depth research was conducted to determine the relationship between WhatsApp usage and employee engagement in the Ministry of Communication and Multimedia Malaysia. This research presents the observation on the level of WhatsApp usage in the Ministry of Communication and Multimedia Malaysia, the understanding of the factors that influence the employee decides to use WhatsApp application, the determination on the level of employee engagement and the relationship between WhatsApp usage and employee engagement. Research findings show that the level WhatsApp of usage in the Ministry of Communication and Multimedia Malaysia is high. On the other hand, the level of employee engagement is also high. The research findings also show that perceived usefulness (r = .62), perceived ease of use (r =.57), social influence (r = .52) and job relevance (r =.64) of WhatsApp usage have positively affected employee engagement.